2012
DOI: 10.1116/1.4709768
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent spin precession measurements in trilayer graphene utilizing co/graphene contacts

Abstract: The temperature dependence of the spin lifetime and spin diffusion coefficient of exfoliated multilayer graphene is measured using nonlocal spin detection and spin precession measurements. Low impedance cobalt contacts are utilized for spin injection and readout. A decrease in spin lifetime with increasing temperature is observed as well as an increase in the spin diffusion coefficient with increasing temperature. This observation provides some insight into the relevant spin relaxation mechanisms that are occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…However, there is a huge sample-to-sample variation in the reported spin lifetimes which vary between tens of ps and several ns at room temperature. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The predicted long intrinsic spin lifetimes of graphene are most likely masked by extrinsic sources of spin scattering and spin dephasing. [16][17][18] In particular, the direct contact of graphene to the underlying wafer and the electronic properties of the deposited spin injection and detection barriers are discussed as key factors that limit spin transport.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a huge sample-to-sample variation in the reported spin lifetimes which vary between tens of ps and several ns at room temperature. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The predicted long intrinsic spin lifetimes of graphene are most likely masked by extrinsic sources of spin scattering and spin dephasing. [16][17][18] In particular, the direct contact of graphene to the underlying wafer and the electronic properties of the deposited spin injection and detection barriers are discussed as key factors that limit spin transport.…”
Section: Introductionmentioning
confidence: 99%
“…Spin lifetimes on the order of μs have been proposed (). However, first experiments using non‐local graphene‐based spin valves on Si/SiO2 revealed typical spin lifetimes below 1 ns and electron mobilities below 10,000thinmathspacenormalcm2(Vsfalse)1 . While the carrier mobilities could significantly be enhanced in suspended graphene devices or in devices in which the graphene sheet is in contact to hexagonal boron nitride (hBN), initial spin transport ex‐periments on those devices still exhibited short spin lifetimes .…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] However, most electrical spin precession experiments measure spin lifetimes shorter than 1 ns and spin diffusion lengths smaller than 10 µm. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Therefore, there has been a strong effort to match spin lifetimes from theory to experimental values. Along this line, theoretical studies propose novel spin scattering mechanisms such as resonant spin scattering by magnetic impurities [24] or entanglement between spin and pseudospin by random spin orbit coupling, [25] which yield calculated spin lifetimes in the experimentally observed range.…”
mentioning
confidence: 99%
“…Long electron spin lifetimes as well as spin diffusion lengths are important prerequisites for enabling advanced spintronic devices. , Theoretically, graphene should fulfill these requirements thanks to its high charge carrier mobilities and its small spin orbit coupling . Accordingly, initial calculations predicted spin lifetimes of up to 1 μs for pristine graphene flakes. , However, for a long time the experimentally measured spin lifetimes at room temperature were shorter than 1 ns. Such short lifetimes are normally also seen at low temperatures, and only seldomly the 1 ns benchmark was reached at such low temperatures. , One explanation for this discrepancy between theoretically predicted and experimentally measured spin lifetimes is given by several recent studies, which demonstrated that the measured spin lifetimes are not intrinsic to graphene but are rather limited by invasive contacts. Hence, much effort was put into the minimization of contact-induced effects and the optimization of the device fabrication. One way to diminish the effect of invasive contacts is the increase of the transport channel length .…”
mentioning
confidence: 99%